The Influence of Religious Figures' Support and Mother's Parenting Patterns on the Incidence of Stunting in the Dry Land Area of the Islands of East Nusa Tenggara Province - Picauly, Intje; Laga Nur, Marselinus; Oematan, Grouse; Marni, Marni; Pellokila, Marthen Robinson; Exposto , Levi Anatolia S.M.; Pacheco , Cipriano do Rosario (Public Health of Indonesia, 2025)
Background : The regional government of Nusa Tenggara Timur (NTT) province has made many efforts to accelerate the reduction of stunting prevalence. However, until now, NTT Province still contributes to a high prevalence of stunting. Objective : The study aims to determine the effect of religious figure support and parenting patterns on stunting incidents in the NTT Islands Dry Land Region. Methods : The research was conducted in May - August 2024 in Batakte Village, West Kupang District, Kupang Regency with a sample of 60 mothers of toddlers and 10 informants who were religious leaders. This type of research is quantitative descriptive using case control study design. The collected data were analyzed univariately and bivariately using che square analysis. Results : The results of the study showed that 96.67% of mothers of toddlers were directly involved in the religious figure innovation program and 91.67% of mothers of toddlers had good food and nutrition parenting patterns. The results of the analysis show that support from religious figures and maternal parenting patterns have an influence (pValue = 0.000 < 0.005) on the incidence of stunting. Further analysis showed that toddlers would be at 36 times greater risk (OR = 36; 95%CL = 8.108-59.894) of experiencing stunting if they did not receive support from religious figures and poor maternal parenting factors gave toddlers a 23 times greater risk (OR = 23; 95%CL = 8.108-39.850) of experiencing stunting. Conclusion: support from religious figures and maternal parenting patterns related to food consumption are important factors in preventing stunting. Suggestion: religious figures together with local governments can carry out nutritional advocacy activities, nutritional counseling and improving nutritional institutional governance to support accelerated steps to overcome stunting problems in dry land and island areas of NTT